Production of Reduced Graphene Oxide Platelets from Graphite Flakes Using the Fenton Reaction as an Alternative to Harmful Oxidizing Agents. (9th January 2019) - Piñas, Jean A. V.; Andrade, Tatiana S.; Oliveira, Andreia T.; Salomão, Pedro E. A.; Rodriguez, Mariandry; Silva, Adilson C.; Oliveira, Henrique S.; Monteiro, Douglas S.; Pereira, Márcio C.
Abstract : The conventional chemical methods to produce graphene using strong oxidizing agents produce toxic gases during synthesis; therefore, these methods do not meet the principles of green chemistry. In this work, an alternative top-down method for the synthesis of a few layers of graphene sheets has been produced by a Fenton reaction- (a mixture of Fe 2+ /H2 O2 ) assisted exfoliation process in water using graphite flakes as a starting material. Based on X-ray diffraction data and Fourier transform infrared (FTIR), Raman spectroscopy, and transmission electron microscopy measurements, it is proposed that the oxidation of graphite by Fenton chemistry facilitates the exfoliation of graphene sheets under mild sonication. Subsequent chemical reduction with ascorbic acid produced a few layers of reduced graphene oxide. Compared to Hummers' method, the Fenton reagent has similar exfoliation efficiency, but due to the Fenton reagent's preference to react with the edges of graphite, the chemical reduction can lead to the formation of less defective reduced graphene oxides. Moreover, since Fe and H2 O2 are cheap and environmentally innocuous, their use in large-scale graphene production is environmentally friendlier than conventional methods that use toxic oxidizing agents.